Correction to: Novel phenotypic variant in the MYH7 spectrum due to a stop-loss mutation in the C-terminal region: a case report - Zsolt Bánfai; Kinga Hadzsiev; Endre Pál; Katalin Komlósi; Márton Melegh; László Balikó; Béla Melegh (BMC, 2017)
Abstract Following publication of the original article [1], the authors requested a correction to the details of one of the co-authors.